1991
DOI: 10.1111/j.1365-3113.1991.tb00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Australian kelp flies Diptera: Coelopidae

Abstract: The morphology of the Coelopidae is considered, particularly in relation to taxonomic characters, terminology, and sexual dimorphism. Taxonomic relationships and family limits are discussed; the Coelopidae appear to be most closely related to the families Helcomyzidae and Dryomyzidae of the superfamily Sciomyzoidea. The following genera are excluded from the Coelopidae: Listriomastax and Apetaenus (Tethinidae), Orygma (Sepsidae), Heterocheila (or Oedoparea, position doubtful). The position of the genera Malaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 19 publications
1
25
1
Order By: Relevance
“…; Bullock & Federle ). This type of setae was also described previously among flies with smooth adhesive pads, including the kelp fly, Amma blancheae (McAlpine ), the syrphid fly, Episyrphus balteatus (Gorb ) or the blowfly, Calliphora vimitoria (Niederegger et al . ); however, their fine structural characteristics were not exactly coincident with the earwig hairy adhesive pads, because the tenent setae of the fly's pulvilli have openings under the endplate where secretions are released (Gorb ).…”
Section: Discussionsupporting
confidence: 78%
“…; Bullock & Federle ). This type of setae was also described previously among flies with smooth adhesive pads, including the kelp fly, Amma blancheae (McAlpine ), the syrphid fly, Episyrphus balteatus (Gorb ) or the blowfly, Calliphora vimitoria (Niederegger et al . ); however, their fine structural characteristics were not exactly coincident with the earwig hairy adhesive pads, because the tenent setae of the fly's pulvilli have openings under the endplate where secretions are released (Gorb ).…”
Section: Discussionsupporting
confidence: 78%
“…The ultrastructure of the adhesive device has been investigated using SEM in several insect groups, such as Coleoptera (Betz 2003), Hymenoptera (Federle et al 2002), Diptera (McAlpine 1991;Gorb 1998;Niederegger et al 2002), and Heteroptera . These researches have demonstrated that insects have developed two distinct mechanisms to attach themselves to a variety of smooth substrates using either smooth or hairy pads (Beutel and Gorb 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This requires the development of a molecular marker system that will enable us to establish paternity from a larger number of males than is currently possible using the Adh marker system. Like most Diptera, female coelopids have multiple and complex spermathecae (McAlpine, 1991;Day and Gilburn, 1997). Female C. frigida typically have three spermathecae, so there is the potential for them to separate sperm from different males.…”
Section: Discussionmentioning
confidence: 99%